Varstrometry for Off-nucleus and Dual Sub-Kpc AGN (VODKA): Long-slit Optical Spectroscopic Follow-up with Gemini/GMOS and Hubble Space Telescope/STIS - Chen, Yu-Ching; Gross, Arran C.; Liu, Xin; Shen, Yue; Zakamska, Nadia L.; Hwang, Hsiang-Chih; Zhuang, Ming-Yang (The Astrophysical journal, 2025)
High spatial and spectral resolution observations are essential for identifying subarcsecond dual and lensed quasars and confirming their redshifts. We present Gemini/Gemini Multi-Object Spectrograph and Hubble Space Telescope/STIS optical spectra for 27 dual quasar candidates selected based on their variability-induced astrometric noise or double detections in Gaia (the Varstrometry for Off-nucleus and Dual sub-Kpc AGN (VODKA) project). From this follow-up, we spectroscopically identify 11 star superpositions and seven dual/lensed quasars. Among the remaining targets, two are likely dual/lensed quasars based on additional radio imaging, while the rest are quasars with unknown companions. Without prior photometric or spectroscopic selection, we find the star contamination rate to be 41%–67%, while the dual/lensed quasar fraction is ≳26% in the follow-up VODKA sample. However, when combined with existing unresolved spectra and spatially resolved two-band color cuts, the dual/lensed quasar fraction can be increased to ≳67%. Our study highlights the need for high-quality spectral data, including a signal-to-noise ratio of at least 20, spatial resolution that is at least twice finer than the source separation, and a spectral resolution of R  ≳ 1000, in order to separate close sources, exclude stellar superpositions, and reliably identify dual quasars.